Integrating Paulo Freire’s Thought and Islamic Values in Vocational Education - Deden Syarif Hidayatulloh; Fuad Hilmi; Muhammad Falikh Rifqi Maulana; Muhammad Irfansyah Maulana (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
Education in Indonesia continues to face challenges, particularly the mismatch between graduates’ skills and labor market demands, alongside increasing social and moral issues. This study seeks to integrate Paulo Freire’s principles of conscientization, humanization, and dialogue with Islamic values of social justice, drawing on the hadith concerning the liberation of Badr War prisoners as a conceptual basis. Using a qualitative approach, the research applies content analysis of Freire’s works and classical hadith sources, supported by field studies at SMK Syahida Tasikmalaya. Findings show that the application of this transformative model in vocational schools encourages active student participation through critical discussions, social reflection, and contextual learning relevant to daily realities, including skills that strengthen family economies. Teachers report that the model assists in adapting lessons to students’ needs, particularly for those who lag behind, though challenges remain in administrative burdens and structural limitations. Students generally respond positively, describing the approach as more interactive, engaging, and socially relevant. This study concludes that integrating Islamic values with Freire’s critical pedagogy provides a strong foundation for vocational education grounded in social justice. Policy implications include strengthening teacher training, making curricula more flexible, and adopting evaluation methods that emphasize social contribution.